Analisis Kesalahan Konjugasi Dalam Karangan Sederhana Bahasa Jerman - Andi Nurfadlia; Syarifah Fathimah Al-Ilmul; Abdul Kasim Achmad (Universitas Negeri Makassar, 2021)
Abstract. The study aims to determine the types of conjugation errors of students in XI MIPA 3 class simple German-language essays. The type of research is descriptive and qualitative. The analytical method used is the error analysis method proposed by Ellis. The data of this research are simple essays written by students that contain conjugations. The data source of this research were students in XI MIPA 3 of SMAN 1 Polewali, which amounted to 30 students. Data were collected through a German writing test. The results of the data analysis showed that there were 86 errors of conjugation that appeared in the test. In Schwache Verben there are 17 types of errors and in Starke Verben there are 11 types of errors